Sternaspis chilensis n. sp., a new species from austral Chilean channels and fjords (Annelida, Sternaspidae) - Díaz-Díaz, Oscar; Rozbaczylo, Nicolás (Zootaxa, 2017)
Sternaspis chilensis n. sp. is described based on specimens collected in channels and fjords of southern Chile and previously identified as Sternaspis scutata (Ranzani, 1817), originally described from the Meditarrean Sea. Sternaspis chilensis n. sp. is described based on the features of the shield with anterior margins rounded and anterior depression shallow; marginal shield chaetal fascicles arranged with an inverted C-shaped pattern; and distribution of the integument papillae. Sternaspis chilensis is widely distributed in the Magellan Province from Estero Reloncaví (41°32’54”S, 72°19’48”W) to Strait of Magellan (53°34’S, 70°04’W), between 50 and 515 m depth.